PENGARUH KINERJA KEUANGAN TERHADAP TOTAL KREDIT PADA BANK SULTRA - Satriana Satriana; Arnadi Chairunnas; Surianto Ilham; Iien Rohmati Nisa (Komunitas Manajemen Kompetitif, 2026)
This study aims to analyze the influence of financial performance on total credit distribution at Bank Sultra. Financial performance is projected through four main variables: Return on Assets (ROA), Operating Expenses to Operating Income (BOPO), Non-Performing Loans (NPL), and Loan to Deposit Ratio (LDR). Using a quantitative research design with a causal associative approach, this study focuses on the causal relationships between variables. The study population includes Bank Sultra's quarterly financial reports for the 2014-2018 period, accessed through the bank's official website. Data analysis was performed using IBM SPSS Statistics version 27 software to ensure the accuracy of hypothesis testing. Partial results indicate that ROA, NPL, and LDR significantly influence total credit, indicating that profitability, asset quality, and liquidity are key determinants of credit policy. Conversely, the BOPO variable was found to have no significant impact on total credit individually. However, simultaneous testing confirmed that ROA, BOPO, NPL, and LDR collectively significantly influence total credit at Bank Sultra. These findings provide important implications for bank management in managing financial ratios to optimize credit expansion. Future researchers are advised to add other independent variables to broaden the scope of the analysis. Keywords: Total Credit, Return on Assets, BOPO, Non-Performing Loans, Loan to Deposit Ratio.